An Examination of Early Intervention Services for Children With Visual Impairments During the COVID-19 Pandemic. (November 2022) - Wild, Tiffany A.; Herzberg, Tina S.; Hicks, Michelle A. C.
Introduction: In the early spring of 2020, governments were beginning to react to the news of a global pandemic being caused by COVID-19. The purpose of this study was to examine the effect of COVID-19 on early intervention services for young children with visual impairments and their families.Methods: Parents of children with visual impairments aged birth to 3 years were asked a series of questions contained in a larger Access and Engagement survey that investigated the experiences of families of children and young adults with visual impairments aged birth to 21 years and professionals that provided educational services.Results: Three overall themes emerged from the data: (1) many changes occurred in the home, (2) early intervention services changed, and (3) planning for the transition to preschool was affected.Discussion: Overall, the changes in education due to the pandemic and initial shutdown resulted in much parental stress. Parents reported that they were stressed and sometimes overwhelmed by the sudden and dramatic changes in their daily lives and how best to help their children in continuing to learn and develop their skills while simultaneously working from home, being caregivers to the other children in the family, and serving as educators and sometimes informal therapists to their children. Many services moved to an online format and were provided remotely.Implications for Practitioners: Service providers should continue to provide services to families and children who have been affected by the COVID-19 pandemic and resulting shutdown while continuing to provide ways to support the social and emotional well-being of their families. Service providers and families should monitor their children's development and learning both now and in the future.